Nesting of arboreal ants (Hymenoptera: Formicidae) in artificial substrates in coffee plantations in the Colombian Andes - López-Dávila, Andrés Jireh; Escobar-Ramírez, Selene; Armbrecht, Inge (Uniciencia, 2021)
Ants can provide pest biocontrol for coffee crops; however, this ecosystem service may decline in intensively managed plantations due to the loss of nesting resources. Considering how to increase the number of ants, we studied if they nest in different types of artificial substrates attached to coffee bushes both in shade-grown and sun-grown coffee plantations. Three independent tests were conducted at some coffee plantations in southwestern Colombia with the purpose of answering the following questions: 1) Do ants nest in artificial substrates made from recyclable materials? 2) Do the types of substrate (materials and configuration) and coffee management (shade-grown vs. sun-grown coffee) affect colonization rates, richness, and identity of colonizing ants? 3) Does time affect substrate colonization rates? Each experiment independently compared different substrate materials and designs, in both shade and sun-grown coffee. Results showed preference of one of the substrates offered and higher nesting rates in shade-grown plantations. Eight ant species were found nesting in artificial substrates, most of them being arboreal generalists. A higher number of ant species colonized substrates in shade-grown plantations; however, the effect was not statistically significant. Nesomyrmex asper and Crematogaster spp. were always found nesting in both types of plantation. There was a trend to increase nesting activity with time in shade-grown coffee but not in sun-grown coffee. Evidence supports that offering artificial substrates enhances arboreal ant nesting in coffee plantations.